Neuronutrisi dalam Siklus Kehidupan: Tinjauan Naratif tentang Pengaruh Pola Makan terhadap Fungsi Neuropsikologis - Anwar Lubis (Journal of Dietetics Science, 2026)
Dietary habits maintain a fundamental correlation with human neuropsychological function across all stages of the lifespan. The central focus of this research involves the complex biochemical interaction mechanisms between nutritional intake and the central nervous system in modulating mental health and cognitive trajectories. This study aims to map the influence of specific dietary patterns on brain morphological integrity and neuropsychological performance, ranging from the prenatal period to senescence. Scientific findings confirm that during the fetal stage, neural maturation is critically dependent on maternal diet via the regulation of glucose transporters (GLUT) 1 and 3; energy perturbations in these isoforms correlate significantly with an increased risk of neurodevelopmental disorders, such as Autism Spectrum Disorder (ASD) and ADHD. In the adult phase, neuronutrition strategies through anti-inflammatory diets are proven to mediate neuroplasticity during post-stroke rehabilitation. Meanwhile, protocols involving high-dose creatine and docosahexaenoic acid (DHA) supplementation effectively mitigate the cerebral "energy crisis" following concussions in athletes. Furthermore, low-glutamate dietary interventions show clinical efficacy in reducing depressive symptoms in Gulf War Illness (GWI) veterans by decreasing NMDA receptor excitotoxicity. In the elderly, the Mediterranean diet plays a protective role against cognitive decline and Alzheimer’s disease associated with decreased cerebral GLUT expression. It is recommended that integrated personalized neuronutrition protocols be adopted as a standard adjuvant strategy in the prevention and rehabilitation of neurological disorders across generations globally.